Experimental study on mechanical properties of double-layer damped liquid storage tanks with various isolation devices - Xiang Li; Lei Xu; Fa Yang; Li-jie Zhu; Bo-lin Wang; Zheng Lu (Soil Dynamics and Earthquake Engineering, 2026)

Effects of exogenous N-acyl-homoserine lactones on biofilm formation by denitrifying bacteria and denitrification start-up in sequencing batch biofilm reactors - Zhi-fei Li; Meng-yuan Yu; Jun-lin Li; Jun Xie; Xiang-ju Cheng; Wang-bao Gong; Kai Zhang; Guang-jun Wang; Yun Xia; Wen-ping Xie; Quan-fa Zhong; Hong-yan Li; et al. (Journal of Environmental Chemical Engineering, 2026)

Chronic exposure to low-dose cadmium disrupts spermatogenesis in mice through ectoplasmic specialization damage - Yue Li; Zi-Fa Li; Bo Qiu; Kai Chen; Tian-Lin Zhang; Hai-Peng Wang; Lin Wang (Journal of Environmental Sciences, 2026)

Opisoma menchikoffi Dubar, 1948: New occurrences from the Lower Jurassic of the High Atlas, Morocco and Tethyan Himalaya, southern Xizang (Tibet), China - Fu-Lin Li; Kai Ye; Xin Rao; Zhong Han; Cheng-Gang Wang; Xiong-Wei Zeng; Long Wang; Hao Liu; Zong-Xin Wang; Fa-Fu Wu; Kun Liang; Wen-Kun Qie (Palaeoworld, 2026)

Ultrasonic-vacuum combined effects on Antarctic krill oil oxidation stability: Potential mechanisms of oxygen reduction and influence on reverse micelle - Xue-Chen Pei; Fa-Wen Yin; Chang-Qiang Leng; Xin-Miao Wang; Qian Wang; Hui-Lin Liu; Bei-Wei Zhu; Da-Yong Zhou (Food Chemistry, 2026)

Correction: Severe enterovirus A71 pathogenesis and immune responses in human nucleolin transgenic mice - Nien-En Hsiao; Ya-Fang Wang; Yi-Chen Lin; Wei-Ting Chou; Li-Jin Hsu; Shih-Min Wang; Jen-Ren Wang; Ming-Derg Lai; Shun-Hua Chen; Chuan-Fa Chang (Medical Microbiology and Immunology, 2025)

Severe enterovirus A71 pathogenesis and immune responses in human nucleolin transgenic mice - Nien-En Hsiao; Ya-Fang Wang; Yi-Chen Lin; Wei-Ting Chou; Li-Jin Hsu; Shih-Min Wang; Jen-Ren Wang; Ming-Derg Lai; Shun-Hua Chen; Chuan-Fa Chang (Medical Microbiology and Immunology, 2025)

Integration of critical state theory into a micromechanical model for granular materials accounting for fabric evolution - Hai-Lin Wang; Xiaoqiang Gu; Zhen-Yu Yin; Chao-Fa Zhao (Computers and Geotechnics, 2025)

Bipolar membrane electrodialysis for producing acid and alkali from concentrated seawater: Industrial application in Bohai Sea, China - Jia-Wang Qin; Shun Tang; Jia-Lin Shi; Teng-Fei Zhang; Lu Yang; Fang Wang; Liang Yin; Yuan-Fa Zhuang (Journal of Water Process Engineering, 2025)

Revealing the oxidation mechanism of Antarctic krill oil induced by metal ion: Focusing on the influence of reverse micelles - Xue-Chen Pei; Fa-Wen Yin; Meng-Ling Jin; Xin-Miao Wang; Hui-Lin Liu; Liang Song; Bei-Wei Zhu; Da-Yong Zhou (Food Chemistry, 2025)

Mechanistic insights into endometriosis: roles of Streptococcus agalactiae and L-carnitine in lesion development and angiogenesis - Yuan Zhuang; Ting Lyu; Yang Chen; Wei Li; Lei Tang; Shi-ping Xian; Peng-fei Yang; Lijie Wang; Qian-qian Zhang; Chaoming Mei; Yu-jing Lin; Zhixiang Yan; et al. (Angiogenesis, 2025)

Associations of exposure to arsenic species and endogenous sex hormones with oral cancer: a hospital-based study in Southeastern China - Na Wang; Wenting Zhang; Haoyuan Song; Weihai Huang; Fa Chen; Fengqiong Liu; Yulan Lin; Yu Qiu; Bin Shi; Lisong Lin; Jing Wang; Baochang He (Environmental Pollution, 2025)

Correction to: Comparison of Long‑Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2025)

Recurrence of Cerebral Arteriovenous Malformation Following Complete Obliteration Through Endovascular Embolization - Qiang Hao; Haibin Zhang; Heze Han; Hengwei Jin; Li Ma; Ruinan Li; Zhipeng Li; Anqi Li; Kexin Yuan; Qinghui Zhu; Ke Wang; Runting Li; et al. (Translational Stroke Research, 2025)

The change rule of lipid oxidation and hydrolysis driven via water in Antarctic krill oil: Based on association colloid formation - Xue-Chen Pei; Xiang-Bo Zeng; De-Yang Li; Xin-Miao Wang; Fa-Wen Yin; Hui-Lin Liu; Da-Yong Zhou (Food Chemistry, 2025)

Research progress of electrospinning in food field: A review - Fa-Lin Sun; Ming-Yue Zhao; Yue Li; Zhi-Ying Li; Xiu-Jun Li; Nuo Wang; Bo-Wen Hu; Hao-Yu Xue; Min Zhao; Jin-Long Tian (Food Hydrocolloids, 2025)

A multirisk-rescued biomimetic nanozyme against periodontitis via inflammation targeting and microenvironment reprogramming - Lin Li; Rui-Xin Wu; Jia Wang; Rui Jin; Xin-Yu Zhang; Mei Xu; Si-Yao Li; Rui Gao; Bei-Min Tian; Xiao-Tao He; Fa-Ming Chen; Yuan Yin (Chemical Engineering Journal, 2025)

Comparison of Long-Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2024)

Analytical behavior of concrete-filled steel tubular pile used in coastal wharf structure subjected to combined loads - Lan Lin; Fa-cheng Wang (Ocean Engineering, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

The effects of repeated freezing and thawing on bovine sperm morphometry and function - Chang-Guo Min; Xin Ma; Yu-Chan Wang; Cheng-Kun Zhong; Chong-shan Yuan; Kai-Yan Zhang; Cheng-Lin Zhan; Sheng-Kui Hou; Xin-Hai Wang; Jun Wang; Jing Zhao; Yi Fang; et al. (Cryobiology, 2024)

3D network of zinc powder woven into fibre filaments for dendrite-free zinc battery anodes - Lin Sha; Bin-Bin Sui; Peng-Fei Wang; Zhe Gong; Yu-Hang Zhang; Yu-Han Wu; Li-Na Zhao; Jun-Jie Tang; Fa-Nian Shi (Chemical Engineering Journal, 2024)

Effective degradation of zearalenone by dye-decolorizing peroxidases from Pleurotus ostreatus and its metabolic pathway and toxicity analysis - Shuai Ding; Chen Lin; Qiuyun Xiao; Fa Feng; Junfeng Wang; Xing Zhang; Shengjing Yang; Lingling Li; Fei Li (Science of The Total Environment, 2024)

Technological diversity in the tropical-subtropical zone of Southwest China during the terminal Pleistocene: excavations at Fodongdi Cave - Fa-Xiang Huan; Shi-Xia Yang; Feng Gao; Xin-Ying Zhou; Jian-Ping Yue; Yu-Xiu Zhang; Jin-Xu Wu; Qi-Jun Ruan; Kai-Wei Qiu; Jing-wen Xu; Nai-Ru Lin; Yi-Ren Wang; et al. (Archaeological and Anthropological Sciences, 2024)

Eudesmane-type sesquiterpenoids from the aerial parts of Artemisia lavandulaefolia and their anti-pancreatic cancer activities - Lin-Fen Ding; Guo-Xian Hu; Yu-Yao Liu; Qiu-Hua Wang; Zhang-Juan Li; Meng-Xia Shen; Gui-Fa Zhu; Xing-De Wu; Jia Su (Phytochemistry, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Investigation of analytical behavior of concrete filled steel tubular (CFST) offshore rock-socketed pile under lateral load - Lan Lin; Fa-cheng Wang (Ocean Engineering, 2023)

Short- and medium-chain chlorinated paraffins in urban road dust of Shanghai, China: concentrations, source apportionment and human exposure assessment - Xue-Tong Wang; Cheng-Lin Wang; Ying Zhou; Guo-Fa Ren; Rui Fu; Jing An (Environmental Geochemistry and Health, 2023)

Effect of Tyrosol Acyl Esters on the Antioxidant Status of Mussel ( Mytilus edulis ) Oil During Accelerated Oxidative Storage - Qian Wang; Mo-Tong Zhang; Xin-Miao Wang; Guan-Hua Zhao; Yuan-Yuan Hu; Fa-Wen Yin; Hui-Lin Liu; Xiao-Yang Liu; Da-Yong Zhou (Journal of Aquatic Food Product Technology, 2023)

Isoquinoline alkaloids from Corydalis edulis Maxim. Exhibiting insulinotropic action - Zhi-Tian Peng; Hui-Xia Huo; Ling-Hui Chao; Yue-Lin Song; Di-Fa Liu; Zhang-Wei Wang; Yuan Zhang; Yun-Fang Zhao; Peng-Fei Tu; Jiao Zheng; Jun Li (Phytochemistry, 2023)

Glyphosate-induced autophagy inhibition results in hepatic steatosis via mediating epigenetic reprogramming of PPARα in roosters - Cai-Yu Lian; Sheng Wei; Zi-Fa Li; Shu-Hui Zhang; Zhen-Yong Wang; Lin Wang (Environmental Pollution, 2023)

A 90-Day Prognostic Model Based on the Early Brain Injury Indicators after Aneurysmal Subarachnoid Hemorrhage: the TAPS Score - Runting Li; Fa Lin; Yu Chen; Junlin Lu; Heze Han; Li Ma; Yahui Zhao; Debin Yan; Ruinan Li; Jun Yang; Shihao He; Zhipeng Li; et al. (Translational Stroke Research, 2023)

Highly selective monoclonal antibody-based fluorescence immunochromatographic assay for the detection of fenpropathrin in vegetable and fruit samples - Zi-Hong Xu; Jun-Kai Wang; Qiu-Xiong Ye; Lin-Feng Jiang; Hao Deng; Jun-Fa Liang; Run-Xi Chen; Wei Huang; Hong-Tao Lei; Zhen-Lin Xu; Lin Luo (Analytica Chimica Acta, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Natural component plumbagin as a potential antibacterial agent against Streptococcus agalactiae infection - Ai‐Guo Huang; Lin‐Jun Su; Wei‐Hao He; Fa‐Li Zhang; Chao‐Shuai Wei; Ying‐Hui Wang (Journal of Fish Diseases, 2022)
Streptococcus agalactiae , also known as Group B Streptococcus (GBS), can infect humans, terrestrial animals and fish. The emergence of bacterial resistance of S. agalactiae to antibiotics leads to an urgent need of exploration of new antimicrobial agents. In the study, the antibacterial activity of natural component plumbagin (PLB) against S. agalactiae was investigated in vitro and in vivo. The results showed that the minimal inhibitory concentration (MIC) of PLB against S. agalactiae was 8 mg/L. The growth curve assay revealed that PLB could inhibit the growth of S. agalactiae . In addition, the time‐killing curve showed that S. agalactiae was killed almost completely by 2‐fold MIC of PLB within 12 h. Transmission electron microscopy results showed obvious severe morphological destruction and abnormal cells of S. agalactiae after treated with PLB. The pathogenicity of S. agalactiae to zebrafish was significantly decreased after preincubation with PLB for 2 h in vitro, further indicating the bactericidal activity of PLB. Interestingly, PLB could kill S. agalactiae without inducing resistance development. Furthermore, pretreatment and post‐treatment assays suggested that PLB also exhibited the antibacterial activity against S. agalactiae infection in vivo by effectively reducing the bacterial load and improving the survival rate of S. agalactiae ‐infected zebrafish. In summary, PLB had potent antibacterial activity against S. agalactiae in vitro and in vivo, and it could be an excellent antimicrobial candidate to prevent and control S. agalactiae infection.

Occurrence, source apportionment, and carcinogenic risk assessment of polycyclic aromatic hydrocarbons in urban road dusts in Shanghai - Xue-Tong Wang; Rui Fu; Ying Zhou; Cheng-Lin Wang; Guo-Fa Ren; Xiao-Li Wang; Hui Li (Environmental Science and Pollution Research, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Impact of prophylactic/preemptive donor lymphocyte infusion and intensified conditioning for relapsed/refractory leukemia: a real-world study - Yu Wang; Qi-Fa Liu; De-Pei Wu; Jing-Bo Wang; Xi Zhang; Heng-Xiang Wang; Feng Gao; Shun-Qing Wang; Zi-Min Sun; Jian Ouyang; Kai-Lin Xu; Su-Jun Gao; et al. (Science China Life Sciences, 2020)

Lactobacillus plantarum PS128 Ameliorated Visceral Hypersensitivity in Rats Through the Gut–Brain Axis - Yen-Wenn Liu; Yen-Po Wang; Hsu-Fang Yen; Pei-Yi Liu; Wen-Jian Tzeng; Chia-Fen Tsai; Han-Chieh Lin; Fa-Yauh Lee; One-Jang Jeng; Ching-Liang Lu; Ying-Chieh Tsai (Probiotics and Antimicrobial Proteins, 2020)

Taxonomy of the order Mononegavirales: update 2019 - Gaya K. Amarasinghe; María A. Ayllón; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Camila Chabi-Jesus; et al. (Archives of Virology, 2019)

Taxonomy of the order Mononegavirales: second update 2018 - Piet Maes; Gaya K. Amarasinghe; María A. Ayllón; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Kartik Chandran; et al. (Archives of Virology, 2019)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Problems of classification in the family Paramyxoviridae - Bert Rima; Peter Collins; Andrew Easton; Ron Fouchier; Gael Kurath; Robert A. Lamb; Benhur Lee; Andrea Maisner; Paul Rota; Lin-Fa Wang (Archives of Virology, 2018)

ACOS5 is required for primexine formation and exine pattern formation during microsporogenesis in Arabidopsis - Hui-hui Xie; Lin Chen; Fa-qing Xu; Wan-sheng Guo; Shui Wang; Zhong-nan Yang; Sen Zhang (Journal of Plant Biology, 2017)

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Associations Between Hepatic Functions and Plasma Amyloid-Beta Levels—Implications for the Capacity of Liver in Peripheral Amyloid-Beta Clearance - Ye-Ran Wang; Qing-Hua Wang; Tao Zhang; Yu-Hui Liu; Xiu-Qing Yao; Fan Zeng; Jing Li; Fa-Yin Zhou; Lin Wang; Jia-Chuan Yan; Hua-Dong Zhou; Yan-Jiang Wang (Molecular Neurobiology, 2017)

Taxonomy of the order Mononegavirales: update 2016 - Claudio L. Afonso; Gaya K. Amarasinghe; Krisztián Bányai; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Nicolás Bejerman; Kim R. Blasdell; François-Xavier Briand; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; et al. (Archives of Virology, 2016)

Erratum to: Injection of Aβ1-40 into hippocampus induced cognitive lesion associated with neuronal apoptosis and multiple gene expressions in the tree shrew - Na Lin; Liu-Lin Xiong; Rong-ping Zhang; Hong Zheng; Lei Wang; Zhong-Yi Qian; Piao Zhang; Zhi-wei Chen; Fa-Bao Gao; Ting-Hua Wang (Apoptosis, 2016)

Injection of Aβ1-40 into hippocampus induced cognitive lesion associated with neuronal apoptosis and multiple gene expressions in the tree shrew - Na Lin; Liu-Lin Xiong; Rong-ping Zhang; Hong Zheng; Lei Wang; Zhong-Yi Qian; Piao Zhang; Zhi-wei Chen; Fa-Bao Gao; Ting-Hua Wang (Apoptosis, 2016)

Endoplasmic Reticulum Protein 29 Protects Axotomized Neurons from Apoptosis and Promotes Neuronal Regeneration Associated with Erk Signal - Yun-Hui Zhang; Visar Belegu; Yu Zou; Fang Wang; Bao-Jiang Qian; Ran Liu; Ping Dai; Wei Zhao; Fa-Bao Gao; Lei Wang; Li-Mei Cao; John W. McDonald; et al. (Molecular Neurobiology, 2015)

TLR1 expression in mouse brain was increased in a KA-induced seizure model - Fa-Xiang Wang; Shi-Yong Liu; Xin Zheng; Xin Chen; Lin-Xiang Lu; Bin Chen; Xiao-yi Xiong; Hai-Feng Shu; Qing-Wu Yang; Hui Yang (Inflammation Research, 2015)

Construction of an integrative linkage map and QTL mapping of grain yield-related traits using three related wheat RIL populations - Fa Cui; Chunhua Zhao; Anming Ding; Jun Li; Lin Wang; Xingfeng Li; Yinguang Bao; Junming Li; Honggang Wang (Theoretical and Applied Genetics, 2014)

Nyamiviridae: Proposal for a new family in the order Mononegavirales - Jens H. Kuhn; Sadia Bekal; Yíngyún Caì; Anna N. Clawson; Leslie L. Domier; Marieke Herrel; Peter B. Jahrling; Hideki Kondo; Kris N. Lambert; Kathie A. Mihindukulasuriya; Norbert Nowotny; Sheli R. Radoshitzky; et al. (Archives of Virology, 2013)

Conditional and unconditional QTL mapping of drought-tolerance-related traits of wheat seedling using two related RIL populations - HONG ZHANG; FA CUI; LIN WANG; JUN LI; ANMING DING; CHUNHUA ZHAO; YINGUANG BAO; QIUPING YANG; HONGGANG WANG (Journal of Genetics, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Tectonic mechanism of the Suining (Ms5.0) earthquake, center of Sichuan Basin, China - Rong-jun Zhou; Yong Li; Laurence Svirchev; Yong-jiu Zhang; Deng-fa He; Yu-lin He; Pei-lin Zhao; Zan-jun Wang; Feng Long; Jin-rong Su; Shi-yuan Wang; Ming-jian Liang; et al. (Journal of Mountain Science, 2013)

Conditional QTL mapping of protein content in wheat with respect to grain yield and its components - LIN WANG; FA CUI; JINPING WANG; LI JUN; ANMING DING; CHUNHUA ZHAO; XINGFENG LI; DESHUN FENG; JURONG GAO; HONGGANG WANG (Journal of Genetics, 2012)

Antigen capture ELISA system for henipaviruses using polyclonal antibodies obtained by DNA immunization - Yoshihiro Kaku; Akira Noguchi; Glenn A. Marsh; Jennifer A. Barr; Akiko Okutani; Kozue Hotta; Boldbaatar Bazartseren; Christopher C. Broder; Akio Yamada; Satoshi Inoue; Lin-Fa Wang (Archives of Virology, 2012)

QTL detection of seven spike-related traits and their genetic correlations in wheat using two related RIL populations - Fa Cui; Anming Ding; Jun Li; Chunhua Zhao; Lin Wang; Xiuqin Wang; Xiaolei Qi; Xingfeng Li; Guoyu Li; Jurong Gao; Honggang Wang (Euphytica, 2012)

Dew water isotopic ratios and their relationships to ecosystem water pools and fluxes in a cropland and a grassland in China - Xue-Fa Wen; Xuhui Lee; Xiao-Min Sun; Jian-Lin Wang; Zhong-Min Hu; Sheng-Gong Li; Gui-Rui Yu (Oecologia, 2012)

QTL detection of seven quality traits in wheat using two related recombinant inbred line populations - Jun Li; Fa Cui; An-ming Ding; Chun-hua Zhao; Xiu-qin Wang; Lin Wang; Yin-guang Bao; Xiao-lei Qi; Xing-feng Li; Ju-rong Gao; De-shun Feng; Hong-gang Wang (Euphytica, 2012)

Wheat kernel dimensions: how do they contribute to kernel weight at an individual QTL level? - FA CUI; ANMING DING; JUN LI; CHUNHUA ZHAO; XINGFENG LI; DESHUN FENG; XIUQIN WANG; LIN WANG; JURONG GAO; HONGGANG WANG (Journal of Genetics, 2011)

Expression patterns of prion protein gene in differential genotypes sheep: quantification using molecular beacon real-time RT-PCR - Chuan Wang; Run Wu; Fa-Di Li; Lei Liu; Xiao-Li Zhang; Chun-Lin Zhao; Xiao-Long Diao; Hong-Wei Guan (Virus Genes, 2011)

Conditional QTL mapping for plant height with respect to the length of the spike and internode in two mapping populations of wheat - Fa Cui; Jun Li; Anming Ding; Chunhua Zhao; Lin Wang; Xiuqin Wang; Sishen Li; Yinguang Bao; Xingfeng Li; Deshun Feng; Lingrang Kong; Honggang Wang (Theoretical and Applied Genetics, 2011)

Arbuscular mycorrhizal fungal community structure and diversity in response to long-term fertilization: a field case from China - Fa Yuan Wang; Jun Li Hu; Xian Gui Lin; Sheng Wu Qin; Jun Hua Wang (World Journal of Microbiology and Biotechnology, 2011)

Ecotoxicity assessment of aged petroleum sludge using a suite of effects-based end points in earthworm Eisenia fetida - Shi-Jie Wang; Zeng-Guang Yan; Guan-Lin Guo; Gui-Lan Lu; Qun-Hui Wang; Fa-Sheng Li (Environmental Monitoring and Assessment, 2010)

Angiotensin-converting enzyme 2 (ACE2) proteins of different bat species confer variable susceptibility to SARS-CoV entry - Yuxuan Hou; Cheng Peng; Meng Yu; Yan Li; Zhenggang Han; Fang Li; Lin-Fa Wang; Zhengli Shi (Archives of Virology, 2010)

Immunoglobulin heavy chain diversity in Pteropid bats: evidence for a diverse and highly specific antigen binding repertoire - Michelle L. Baker; Mary Tachedjian; Lin-Fa Wang (Immunogenetics, 2010)

Provenance and thermal history of the Bayan Har Group in the western‐central Songpan–Ganzi–Bayan Har terrane: Implications for tectonic evolution of the northern Tibetan Plateau - Guo‐Can Wang; Robert P. Wintsch; John I. Garver; Mary Roden‐Tice; She‐Fa Chen; Ke‐Xin Zhang; Qi‐Xiang Lin; Yun‐Hai Zhu; Shu‐Yuan Xiang; De‐Wei Li (Island Arc, 2009)
Triassic turbidites dominate the Songpan–Ganzi–Bayan Har (SGBH) terrane of the northern Tibetan Plateau. U‐Pb dating on single detrital zircon grains from the Triassic Bayan Har Group turbidites yield peaks at 400–500 m.y., 900–1000 m.y., 1800–1900 m.y., and 2400–2500 m.y., These results are consistent with recently published U‐Pb zircon ages of pre‐Triassic bedrock in the East Kunlun, Altyn, Qaidam, Qilian and Alaxa areas to the north, suggesting that provenance of the Bayan Har Group may include these rocks. The similarities in the compositions of the lithic arkosic sandstones of the Bayan Har Group with the sandstones of the Lower‐Middle Triassic formations in the East Kunlun terrane to the north also suggests a common northern provenance for both. A well exposed angular unconformity between the Carboniferous–Middle Permian mélange sequences and the overlying Upper Permian or Triassic strata indicates that regional deformation occurred between the Middle and Late Permian. This deformation may have been the result of a soft collision between the Qiangtang terrane and the North China Plate and the closure of the Paleo‐Tethyan oceanic basin. The Bayan Har Group turbidites were then deposited in a re‐opened marine basin on a shelf environment. Fission‐track dating of detrital zircons from the Bayan Har Group sandstones revealed pre‐ and post‐depositional age components, suggesting that the temperatures did not reach the temperatures necessary to anneal retentive zircon fission tracks (250–300°C). A 282–292 m.y. peak age defined by low U concentration, retentive zircons likely reflects a northern granitic source. Euhedral zircons from two lithic arkoses with abundant volcanic fragments in the southern area yielded a ∼237 m.y. zircon fission track (ZFT) peak age, likely recording the maximum age of deposition. A dominant post‐depositional 170–185 m.y. ZFT peak age suggests peak temperatures were reached in the Early Jurassic. Some samples appear to record a younger thermal event at ∼140 m.y., a short lived event that apparently affected only the least retentive zircons.

Fluorescent co-localization of PTS1 and PTS2 and its application in analysis of the gene function and the peroxisomal dynamic in Magnaporthe oryzae - Jiao-yu Wang; Xiao-yan Wu; Zhen Zhang; Xin-fa Du; Rong-yao Chai; Xiao-hong Liu; Xue-qin Mao; Hai-ping Qiu; Yan-li Wang; Fu-cheng Lin; Guo-chang Sun (Journal of Zhejiang University-SCIENCE B, 2008)

Mitochondrial anchoring of PKCα by PICK1 confers resistance to etoposide-induced apoptosis - Wei-Li Wang; Sheau-Farn Yeh; Eagle Yi-Kung Huang; Yu-Ling Lu; Chun-Fa Wang; Chi-Ying F. Huang; Wey-Jinq Lin (Apoptosis, 2007)

Expression of truncated phosphoproteins of Nipah virus and Hendra virus in Escherichia coli for the differentiation of henipavirus infections - Ji-Ming Chen; Koon Chu Yaiw; Meng Yu; Lin-Fa Wang; Qing-Hua Wang; Gary Crameri; Zhi-Liang Wang (Biotechnology Letters, 2007)

Changes of cell proliferation and differentiation in the developing brain of mouse - Lin Qiu; Chang-Lian Zhu; Xiao-Yang Wang; Fa-Lin Xu (Neuroscience Bulletin, 2007)

Peptide mimotopes of phomopsins: Identification, characterization and application in an immunoassay - Meng Yu; Khin Than; Steve Colegate; Brian Shiell; Wojtek P. Michalski; Stephen Prowse; Lin-Fa Wang (Molecular Diversity, 2005)

The July 14, 2003 Qianjiangping landslide, Three Gorges Reservoir, China - Fa-Wu Wang; Ye-Ming Zhang; Zhi-Tao Huo; Tatsunori Matsumoto; Bo-Lin Huang (Landslides, 2004)

Arbuscular mycorrhizal status of wild plants in saline-alkaline soils of the Yellow River Delta - Jian-Min Zhou; Xian-Gui Lin; Fa-Yuan Wang; Run-Jin Liu (Mycorrhiza, 2004)